An Overview of Titanium Oxide Nanoparticles, Chareacterisation, ‎Synthesis and Potential Applications (Journal of University of Babylon for Engineering Sciences, 2022)
The nanoparticles  has given a serious concern  due to  its novel and attractive properties  due to its  small size and high specific surface area. These outstanding features has allow for nanoparticles to potentially utilized for many applications. Aconsiderable attention has recently fouced on Titanium oxide nanoparticles because of  their  outstanding applications including gas sensors, electronic devices, optical magnetic recording, catalysis, and potentially used in biomedical applications. Various  methods have been employed in order to generate TiO2 (NPs) of  required size and morphology to potentially use in many field sectors. In this review, the importance, structure and properties of TiO2 nanoparticles are summarised and demonstrated. Recently, a number of scientific researchers  have been developed synthesis methods for obtaining titanium oxide nanoparticles are classified into basically methods:  physical, chemical  and biological synthesis. A detailed overiew of different applications for titanium oxide nanopartciles are presented.